Quinoline modified nano white carbon black zinc ion fluorescent probe based on surface imprinting technology and application thereof
By using surface ion blotting technology to fix quinoline ligands on the surface of nanosalpha carbon black, a quinoline-modified nanosalpha carbon black zinc ion fluorescent probe was prepared, which solved the problem of separation and recovery of the existing technology of small and medium-sized fluorescent probes, and realized the selective fluorescence detection of zinc ions in water.
Patent Information
- Application Number
- CN202411924742.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-08
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art small and medium-sized fluorescent probes have problems such as difficulty in separating and recycling zinc ions in water, poor reusability and poor solubility, and traditional heavy metal adsorption materials have problems with non-selective adsorption.
The quinoline ligand imprint cavity structure was fixed on the surface of nanosalpha carbon black particles by surface ion blotting technology, and a quinoline-modified nanosalpha carbon black zinc ion fluorescent probe was prepared to achieve selective recognition and adsorption enrichment of zinc ions in water.
The selective fluorescence identification and detection of zinc ions in water is realized, the operation is simple and the material can be recycled, and the problem of separation and recycling of probes in the prior art is solved, and the selectivity of detection is improved.
Smart Images

Figure CN119775997A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of organic functional modification of nano-silica surface, and in particular to a quinoline-modified nano-silica zinc ion fluorescent probe based on surface imprinting technology and application thereof, so as to realize selective fluorescent identification and detection of zinc ions in water. Background Art
[0002] Zinc is widely used in industries such as home appliances, automobiles, and electronics, and is also the second most abundant essential trace element in the human body. However, excessive intake of zinc ions can cause diarrhea, nausea and vomiting, and even cause digestive tract diseases. Currently, a variety of detection methods have been developed, such as atomic absorption spectroscopy and inductively coupled plasma spectroscopy, but these methods are costly, complex to operate, and require bulky equipment, making them unsuitable for on-site detection. Therefore, there is an urgent need to develop a low-cost, easy-to-operate, and highly sensitive method to detect low concentrations of zinc ions in water.
[0003] Small molecule metal ion fluorescent probes are generally composed of recognition groups, fluorescent groups and linkers. They can specifically bind to target metal ions and reflect their presence and concentration through changes in fluorescent signals. This type of probe has broad prospects in the field of metal ion detection due to its low cost, simple operation, fast response time, high sensitivity and good selectivity. However, existing small molecule probes have problems such as difficulty in separation and recovery, poor reusability and difficulty in removing metal ions from samples. Although many reported zinc ion small molecule fluorescent probes are designed and prepared based on quinoline and its derivatives, these compounds generally have poor solubility in water and often require polar organic solvents to assist solubilization. In recent years, loading fluorophores into nanomaterials has received great attention in the field of detection. Heterogeneous nanocomposites can be dispersed in aqueous solutions to make the functional chromophores uniformly distributed in water. In addition, heterogeneous nanoprobes can be used as adsorbents to remove analytes, and the recovered nanoprobe materials can be easily regenerated by elution of the analyte for reuse.
[0004] Traditional heavy metal adsorption materials use physical or chemical methods to apply heavy metal ions to the surface of the material, but this can easily lead to non-selective adsorption of other coexisting ions. In contrast, ion-imprinted polymer materials form specific imprinted cavities through the copolymerization of template ions with functional monomers and crosslinkers, followed by the removal of template ions. This cavity is highly complementary to the shape and size of the target ions. Surface imprinting technology based on sol-gel technology has also been developed, which can form thin and effective imprinted coating films on the surface of inorganic materials. Nano-silica, as a special nanomaterial, has excellent physical and chemical properties, a high specific surface area, and is easy to be chemically modified, making it an ideal material for the preparation of high-performance surface imprinted adsorbents.
[0005] Most of the reported surface imprinting technologies usually simply introduce chelating groups on high specific surface inorganic carriers to form specific imprinted cavities. Such nanocomposites can only be used for selective adsorption of target metal ions. However, if fluorescent probe molecules are introduced on the carrier surface in combination with surface imprinting technology, not only can specific recognition of target ions in water be achieved, but also selective fluorescence detection and adsorption removal can be performed, showing broad application prospects in the field of environmental protection. Based on this, the present invention utilizes surface ion imprinting technology to prepare quinoline-modified nano-silica zinc ion fluorescent probe materials, and the selective recognition of target zinc ions in water is achieved through this technology, thereby improving the selective fluorescence identification and detection of zinc ions by the material. Summary of the invention
[0006] In view of the limited applicability of small molecule fluorescent probes for detecting target metal ions in the prior art, the present invention provides a quinoline-modified nano-silica zinc ion fluorescent probe based on surface imprinting technology. A quinoline ligand-imprinted cavity structure having high complementarity with zinc ions in shape and size is fixed on the outer surface of nano-silica particles by a surface ion imprinting method, thereby achieving specific recognition and adsorption enrichment of target zinc ions. According to the different positions of the amide bond in the quinoline chromophore substitution, the general structural formula is as follows:
[0007]
[0008] in, Refers to the outer surface of nano-white carbon black particles. It is a specific imprinted cavity structure with high complementarity in shape and size with the zinc ion, and the amide bond is located at one of the four substitution sites of the benzene ring in the quinoline chromophore.
[0009] The present invention further provides a method for preparing the above-mentioned quinoline-modified nano-silica zinc ion fluorescent probe based on surface ion imprinting technology, comprising the following steps:
[0010] Step 1: Add a certain amount of aminoquinoline and triethylamine to a round-bottom flask containing an organic solvent, cool to 0°C and stir magnetically for 20 to 60 minutes, then slowly drop acetyl halide into the solution through a dropping funnel over 20 to 60 minutes; slowly heat the mixed solution to room temperature and stir magnetically for overnight reaction, then remove the organic solvent in the reaction system by vacuum rotary evaporation, and separate and purify the crude product by silica gel column chromatography to obtain AQ-X. The specific synthesis step reaction formula is expressed as follows:
[0011]
[0012] Step 2: Add equal amounts of AQ-X and (3-aminopropyl) triethoxysilane obtained in step 1 to a round-bottom flask containing an organic solvent, stir magnetically to mix evenly, and then add potassium carbonate; stir the reaction solution magnetically and reflux for 12 to 24 hours, refrigerate and stand at 5°C for 12 hours, filter the solution to remove white insoluble matter, and remove the solvent from the filtrate by vacuum rotary evaporation to obtain a yellow oil; dissolve the obtained yellow oil in anhydrous ethanol, add a certain amount of zinc nitrate to the solution as a template imprinted metal ion, wherein the amount of zinc nitrate is 1 / 2 of the amount of (3-aminopropyl) triethoxysilane; control the temperature at 40 to 50°C under nitrogen protection and stir magnetically for 12 to 24 hours, remove ethanol in the reaction system by vacuum rotary evaporation, and obtain a complex AQ(Zn) of quinoline functionalized siloxane coupling agent monomer and zinc ion template. The specific synthesis step reaction formula is expressed as follows:
[0013]
[0014] Step 3, AQ (Zn) in step 2 and acidified fumed nano-silica are dispersed in an organic solvent, and after ultrasonic dispersion, the mixture is magnetically stirred at 60 to 90° C. under nitrogen protection for 12 to 24 hours; after cooling to room temperature, the product is centrifuged, and the obtained solid is washed twice with tetrahydrofuran and then twice with ethanol, and finally vacuum dried to obtain a nano-silica material Si-AQ (Zn) with a surface-modified quinoline chromophore coordinated with zinc ions. The specific synthesis step reaction formula is expressed as follows:
[0015]
[0016] Step 4: Add Si-AQ(Zn) in step 3 to an inorganic acid solution, and after ultrasonic dispersion, magnetic stirring is performed at room temperature for 12 to 24 hours, and the product is centrifuged; the obtained solid is repeatedly washed with deionized water until the washed aqueous solution is close to neutral; and finally, vacuum drying is performed to obtain quinoline-modified nano-silica fluorescent probe Si-AQ-IIA based on surface ion imprinting technology. The specific synthesis step reaction formula is expressed as follows:
[0017]
[0018] As a preferred technical solution of the present invention, the aminoquinoline in step 1 is selected from any one of 5-aminoquinoline, 6-aminoquinoline, 7-aminoquinoline or 8-aminoquinoline; the ratio of the amount of the aminoquinoline substance to the amount of triethylamine is 1:1.0-1.2; the organic solvent is selected from any one of dichloromethane, chloroform, acetone, methanol, anhydrous ethanol, isopropanol, anisole, tetrahydrofuran, dioxane, acetonitrile and N,N-dimethylformamide; the solid-liquid mass volume ratio of the aminoquinoline and the organic solvent is 1:100-150 g / mL; the halogenated acetyl halide is selected from any one of chloroacetyl chloride, bromoacetyl bromide, bromoacetyl chloride and chloroacetyl bromide; the ratio of the amount of the aminoquinoline substance to the amount of the halogenated acetyl halide is 1:1.0-1.2.
[0019] As a preferred technical solution of the present invention, the organic solvent in step 2 is selected from any one of dichloromethane, chloroform, acetone, methanol, anhydrous ethanol, isopropanol, anisole, tetrahydrofuran, dioxane, acetonitrile and N,N-dimethylformamide; the solid-liquid mass volume ratio of the (3-aminopropyl) triethoxysilane and the organic solvent is 1:1:100-150 g / mL L; the molar ratio of the (3-aminopropyl) triethoxysilane and potassium carbonate is 1:1.5-2.5; the solid-liquid mass volume ratio of the (3-aminopropyl) triethoxysilane and ethanol is 1:1:100-150 g / mL.
[0020] As a preferred technical solution of the present invention, the mass ratio of AQ (Zn) and nano-silica in step 3 is 1:1.0-1.5; the organic solvent is selected from any one of dichloromethane, chloroform, acetone, methanol, anhydrous ethanol, isopropanol, anisole, tetrahydrofuran, dioxane, acetonitrile and N,N-dimethylformamide; the solid-liquid mass volume ratio of the nano-silica to the polar organic solvent is 1:100-150 g / mL.
[0021] As a preferred technical solution of the present invention, the inorganic acid solution in step 4 is selected from any one of sulfuric acid, hydrochloric acid and nitric acid solution; the solid-liquid mass volume ratio of the Si-AQ (Zn) to the inorganic acid solution is 1:80-120 g / mL; and the mass concentration of the inorganic acid is 0.3-1.0%.
[0022] The invention discloses an application of a quinoline-modified nano-silica zinc ion fluorescent probe based on surface imprinting technology. The nano-silica zinc ion fluorescent probe combines with zinc ions in water and loads the ions on the surface of the material, and fluorescence enhancement occurs at the same time. Therefore, the quinoline-modified nano-silica zinc ion fluorescent probe based on surface imprinting technology is used for selective fluorescence identification and detection of zinc ions in water.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] The quinoline-modified nano-silica zinc ion fluorescent probe provided by the present invention has a simple preparation method. When quinoline is used as a surface modifier to form a complex with zinc ions, the fluorescent signal can be significantly enhanced. Therefore, the quinoline-modified nano-silica material provided by the present invention is suitable for fluorescent quantitative detection of zinc ions in aqueous solution, is easy to operate, and the material can be recycled.
[0025] The present invention provides a quinoline-modified nano-silica zinc ion fluorescent probe prepared by using surface ion imprinting technology. The surface ion imprinting technology forms a specific recognition site on the surface of the material. The site has high complementarity with the zinc ion in shape and size, and can significantly improve the specific effect with the target zinc ion under the condition of the presence of other interfering ions, effectively improving the selectivity of fluorescent quantitative detection of zinc ions in water bodies, and solving the problem of limited selectivity of nano-composite fluorescent probes for target ion detection in the prior art. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0027] Figure 1 This is a transmission electron microscope photo of Si-AQ-IIA-1 prepared in Example 1;
[0028] Figure 2 The fluorescence emission spectra of Si-AQ-IIA-1 prepared in Example 1 at an excitation wavelength of 328 nm in the presence of different concentrations of zinc ions;
[0029] Figure 3 The fluorescence intensity (425 nm) change of Si-AQ-IIA-1 prepared in Example 1 after adding zinc ions in the presence of interfering ions;
[0030] Figure 4 The fluorescence intensity (425 nm) change of Si-AQ-NIIA prepared in Example 4 after adding zinc ions in the presence of interfering ions; DETAILED DESCRIPTION
[0031] To further disclose the technical solution of the present invention, the technical solution in the embodiment of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiment of the present invention. Obviously, the described embodiment is only a part of the embodiment of the present invention, not all of the embodiments. Based on the embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention.
[0032] Embodiment 1:
[0033] A preparation method of quinoline-modified nano-silica zinc ion fluorescent probe Si-AQ-IIA-1 based on surface imprinting technology, the specific steps are as follows:
[0034] (i) 0.726 g (5.0 mmol) of 8-aminoquinoline and 0.526 g (5.2 mmol) of triethylamine were added to a round-bottom flask containing 80 mL of chloroform, the temperature was lowered to 0°C and magnetically stirred for 30 minutes, and then 0.621 g (5.5 mmol) of chloroacetyl chloride was slowly added dropwise to the above solution through a dropping funnel over 30 minutes; the mixed solution was slowly heated to room temperature and allowed to react overnight with magnetic stirring, and the organic solvent in the reaction system was removed by vacuum rotary evaporation, and the crude product was separated and purified by silica gel column chromatography to obtain AQ-X-1.
[0035] (ii) adding 0.883 g (4.0 mmol) of AQ-X-1 and 0.885 g (4.0 mmol) of (3-aminopropyl) triethoxysilane obtained in step 1 to a round-bottom flask containing 120 mL of acetonitrile, stirring magnetically to mix well, and then adding 1.105 g (8.0 mmol) of potassium carbonate; stirring the reaction solution magnetically under reflux for 18 hours, refrigerating and standing at 5°C for 12 hours, filtering the solution to remove white insoluble matter, and removing the solvent from the filtrate by vacuum rotary evaporation to obtain a yellow oil; dissolving the yellow oil in 120 mL of anhydrous ethanol, adding 0.379 g (2.0 mmol) of zinc nitrate as a template imprinted metal ion to the solution; controlling the temperature at 40°C under nitrogen protection and stirring magnetically for 24 hours, removing ethanol in the reaction system by vacuum rotary evaporation to obtain a complex AQ(Zn)-1 of quinoline functionalized siloxane coupling agent monomer and zinc ion template.
[0036] (III) Dispersing 1.000 g of AQ(Zn)-1 and 1.000 g of acidified fumed nano-silica in step 2 into 120 mL of anhydrous ethanol, and then ultrasonically dispersing and magnetically stirring at 80° C. for 16 hours under nitrogen protection; after cooling to room temperature, the product was centrifuged, and the obtained solid was washed twice with tetrahydrofuran and then twice with ethanol, and finally vacuum dried to obtain the nano-silica material Si-AQ(Zn)-1 with a surface-modified quinoline chromophore coordinated with zinc ions.
[0037] (IV) adding 1.000 g Si-AQ(Zn)-1 in step 3 to 100 mL of 1.0% hydrochloric acid solution, ultrasonically dispersing, magnetically stirring at room temperature for 16 hours, and centrifuging the product; washing the obtained solid with deionized water repeatedly for several times until the washed aqueous solution is close to neutral; finally, vacuum drying is performed to obtain quinoline-modified nano-silica fluorescent probe Si-AQ-IIA-1 based on surface ion imprinting technology, and the structural schematic diagram of the final product is as follows:
[0038]
[0039] Embodiment 2:
[0040] A quinoline-modified nano-silica zinc ion fluorescent probe Si-AQ-IIA-2 based on surface imprinting technology, the specific steps are as follows:
[0041] (i) 0.726 g (5.0 mmol) of 5-aminoquinoline and 0.506 g (5.0 mmol) of triethylamine were added to a round-bottom flask containing 109 mL of dichloromethane, cooled to 0°C and mixed with magnetic stirring for 20 minutes, and then 1.009 g (5.0 mmol) of bromoacetyl bromide was slowly added dropwise to the above solution through a dropping funnel over 60 minutes; the mixed solution was slowly heated to room temperature and allowed to react with magnetic stirring overnight, and then the organic solvent in the reaction system was removed by vacuum rotary evaporation, and the crude product was separated and purified by silica gel column chromatography to obtain AQ-X-2.
[0042] (ii) 1.061 g (4.0 mmol) of AQ-X-2 obtained in step 1 and 0.885 g (4.0 mmol) of (3-aminopropyl) triethoxysilane were added to a round-bottom flask containing 133 mL of tetrahydrofuran, and 1.380 g (10.0 mmol) of potassium carbonate was added after magnetic stirring to mix evenly; the reaction solution was magnetically stirred and refluxed for 24 hours, and then refrigerated and allowed to stand at 5°C for 12 hours, and the solution was filtered to remove the white insoluble matter, and the filtrate was subjected to vacuum rotary evaporation to remove the solvent to obtain a yellow oil; the yellow oil was dissolved in 133 mL of anhydrous ethanol, and 0.379 g (2.0 mmol) of zinc nitrate was added to the solution as a template imprinted metal ion; the temperature was controlled at 50°C under nitrogen protection and magnetic stirring was performed for 18 hours, and the ethanol in the reaction system was removed by vacuum rotary evaporation to obtain a complex AQ(Zn)-2 of quinoline functionalized siloxane coupling agent monomer and zinc ion template.
[0043] (III) Dispersing 1.000 g of AQ(Zn)-2 and 1.500 g of acidified fumed nano-silica in step 2 into 150 mL of acetonitrile, and then ultrasonically dispersing and magnetically stirring at 90° C. for 24 hours under nitrogen protection; after cooling to room temperature, the product was centrifuged, and the obtained solid was washed twice with tetrahydrofuran and then twice with ethanol, and finally vacuum dried to obtain the nano-silica material Si-AQ(Zn)-2 with surface-modified quinoline chromophore coordinated with zinc ions.
[0044] (IV) adding 1.000 g Si-AQ(Zn)-2 in step 3 to 100 mL of 0.3% sulfuric acid solution, ultrasonically dispersing, magnetically stirring at room temperature for 24 hours, and centrifuging the product; washing the obtained solid with deionized water repeatedly until the washed aqueous solution is close to neutral; finally, vacuum drying is performed to obtain quinoline-modified nano-silica fluorescent probe Si-AQ-IIA-2 based on surface ion imprinting technology, and the structural schematic diagram of the final product is as follows:
[0045]
[0046] Embodiment 3:
[0047] A quinoline-modified nano-silica zinc ion fluorescent probe Si-AQ-IIA-3 based on surface imprinting technology, the specific steps are as follows:
[0048] (i) 0.726 g (5.0 mmol) of 6-aminoquinoline and 0.506 g (6.0 mmol) of triethylamine were added to a round-bottom flask containing 109 mL of tetrahydrofuran, cooled to 0°C and magnetically stirred for 60 minutes, and then 0.944 g (6.0 mmol) of bromoacetyl chloride was slowly added dropwise to the above solution through a dropping funnel over 20 minutes; the mixed solution was slowly heated to room temperature and allowed to react with magnetic stirring overnight, and then the organic solvent in the reaction system was removed by vacuum rotary evaporation, and the crude product was separated and purified by silica gel column chromatography to obtain AQ-X-3.
[0049] (ii) 1.061 g (4.0 mmol) of AQ-X-3 obtained in step 1 and 0.885 g (4.0 mmol) of (3-aminopropyl) triethoxysilane were added to a round-bottom flask containing 86 mL of tetrahydrofuran, and 0.828 g (6.0 mmol) of potassium carbonate was added after magnetic stirring to mix evenly; the reaction solution was magnetically stirred and refluxed for 12 hours, and then refrigerated and allowed to stand at 5°C for 12 hours, and the solution was filtered to remove the white insoluble matter, and the filtrate was subjected to vacuum rotary evaporation to remove the solvent to obtain a yellow oil; the yellow oil was dissolved in 86 mL of anhydrous ethanol, and 0.379 g (2.0 mmol) of zinc nitrate was added to the solution as a template imprinted metal ion; the temperature was controlled at 45°C under nitrogen protection and magnetic stirring was performed for 12 hours, and the ethanol in the reaction system was removed by vacuum rotary evaporation to obtain a complex AQ(Zn)-3 of quinoline functionalized siloxane coupling agent monomer and zinc ion template.
[0050] (III) Dispersing 1.000 g of AQ(Zn)-3 and 1.300 g of acidified gas-phase nano-silica in step 2 into 60 mL of dioxane, and stirring the mixture under ultrasonic dispersion and temperature control at 60° C. for 12 hours under nitrogen protection; after cooling to room temperature, the product was centrifuged, and the solid was washed twice with tetrahydrofuran and then twice with ethanol, and finally dried under vacuum to obtain the nano-silica material Si-AQ(Zn)-3 with surface-modified quinoline chromophore coordinated with zinc ions.
[0051] (IV) adding 1.000 g Si-AQ(Zn)-3 in step 3 to 100 mL of 0.5% nitric acid solution, ultrasonically dispersing, magnetically stirring at room temperature for 12 hours, and centrifuging the product; washing the obtained solid with deionized water repeatedly until the washed aqueous solution is close to neutral; finally, vacuum drying is performed to obtain quinoline-modified nano-silica fluorescent probe Si-AQ-IIA-3 based on surface ion imprinting technology, and the structural schematic diagram of the final product is as follows:
[0052]
[0053] Embodiment 4:
[0054] A preparation of a quinoline-modified nano-silica zinc ion fluorescent probe Si-AQ-NIIA based on non-surface imprinting technology, the probe material can be compared with the fluorescence detection performance of the probe prepared based on ion imprinting technology. The difference between this embodiment and the above-mentioned embodiments 1 to 3 is that quinoline bonded with active halogen atoms and siloxane coupling agent nano-silica containing amino functional groups react to obtain a quinoline-modified nano-silica fluorescent probe material. The other conditions of this embodiment refer to Example 1, and the specific steps are as follows:
[0055] (i) 0.726 g (5.0 mmol) of 8-aminoquinoline and 0.526 g (5.2 mmol) of triethylamine were added to a round-bottom flask containing 80 mL of chloroform, the temperature was lowered to 0°C and magnetically stirred for 30 minutes, and then 0.621 g (5.5 mmol) of chloroacetyl chloride was slowly added dropwise to the above solution through a dropping funnel over 30 minutes; the mixed solution was slowly heated to room temperature and allowed to react overnight with magnetic stirring, and the organic solvent in the reaction system was removed by vacuum rotary evaporation, and the crude product was separated and purified by silica gel column chromatography to obtain AQ-X-1.
[0056] (ii) 0.883 g (4.0 mmol) of AQ-X-1 and 0.885 g (4.0 mmol) of (3-aminopropyl) triethoxysilane obtained in step 1 were added to a round-bottom flask containing 120 mL of acetonitrile, and 1.105 g (8.0 mmol) of potassium carbonate was added after magnetic stirring to mix evenly; the reaction solution was magnetically stirred and refluxed for 18 hours, and then refrigerated and allowed to stand at 5°C for 12 hours, and the solution was filtered to remove the white insoluble matter. The filtrate was subjected to vacuum rotary evaporation to remove the solvent to obtain a yellow oily product, which was quinoline AQ-silane bonded with an active halogen atom.
[0057] (III) Dispersing 1.000 g of AQ-silane and 1.000 g of acidified gas-phase nano-silica in step 2 into 120 mL of anhydrous ethanol, and then ultrasonically dispersing and magnetically stirring at 80° C. for 16 hours under nitrogen protection; after cooling to room temperature, the product was centrifuged, and the obtained solid was washed twice with tetrahydrofuran and then twice with ethanol, and finally vacuum dried to obtain quinoline-modified nano-silica zinc ion fluorescent probe Si-AQ-NIIA based on non-surface imprinting technology.
[0058] Example 5: Electron Microscope Characterization
[0059] The morphology of the quinoline-modified nano-silica zinc ion fluorescent probe Si-AQ-IIA-1 based on surface imprinting technology obtained in Example 1 was characterized by transmission electron microscopy. Figure 1 The transmission electron microscope image of Si-AQ-IIA-1 is shown, and its particle size is about 20 nanometers, and there is slight agglomeration during the sample preparation stage. This characterization result shows that the nano-silica Si-AQ-IIA-1 modified by quinoline based on surface imprinting technology exhibits excellent structural stability, and its morphology remains basically unchanged even after chemical modification and acid solution treatment.
[0060] When Si-AQ-IIA-1 was added to an aqueous solution and subjected to 0.5 minutes of ultrasonic treatment, it was effectively dispersed in water, and no significant precipitation was observed in the next half hour. This experimental result strongly verified that the chemically modified silica Si-AQ-IIA-1 exhibited excellent dispersibility in water.
[0061] Example 6: Construction of fluorescent probe
[0062] The present invention studies the fluorescence response performance of Si-AQ-IIA-1 prepared in Example 1 to zinc ions. Specifically, the experiment was carried out at 25°C, and 2.0 mL of zinc ion solutions of different concentrations were added to 2.0 mL of Si-AQ-IIA-1 stock dispersion (concentration of 0.2 mg / mL), and after uniform mixing, the concentration of Si-AQ-IIA-1 became 0.1 mg / mL. Subsequently, the pH value of the solution was adjusted to 6.0, and sufficient dispersion was achieved by ultrasonic oscillation. Then, the dispersion was quickly transferred to a quartz cuvette to record its fluorescence emission spectrum at an excitation wavelength of 328 nm.
[0063] like Figure 2 As shown in the figure, as the zinc ion concentration gradually increased from 0 mg / L to 2 mg / L, the fluorescence emission intensity of the Si-AQ-IIA-1 dispersion showed a continuous upward trend. During this process, the shape of the emission band remained basically unchanged, and the maximum emission wavelength was maintained at about 425 nm. Finally, the maximum fluorescence emission intensity of the Si-AQ-IIA-1 aqueous dispersion in the presence of zinc ions reached 3.5 times the initial intensity. Thereafter, even if the concentration of zinc ions continued to increase, the decrease in fluorescence intensity was not significant. Therefore, Si-AQ-IIA-1 can be used as an effective zinc ion fluorescence detection probe.
[0064] Example 7: Selectivity of fluorescence detection
[0065] The present invention studies the selectivity of the fluorescence detection of zinc ions by Si-AQ-IIA-1 prepared in Example 1. The experiment was set at 25°C, and 2.0 mL of an interfering ion solution with a concentration of 4 mg / L was added to 2.0 mL of the Si-AQ-IIA-1 reserve dispersion (concentration of 0.2 mg / mL) prepared in Example 1. After mixing evenly, the concentration of Si-AQ-IIA-1 became 0.1 mg / mL, the pH value of the solution was adjusted to 6.0, and uniform dispersion was achieved by ultrasonic oscillation. Afterwards, the resulting suspension was transferred to a quartz cuvette, and the fluorescence emission intensity at 425 nm was recorded under 328 nm excitation light. In addition, a mixed solution containing 4 mg / L interfering ions and 4 mg / L zinc ions was prepared, and the above test process was repeated. In order to evaluate the effect of surface ion imprinting technology on the selectivity of fluorescence detection, Si-AQ-NIIA prepared by non-ionic imprinting technology was used as a comparison nanoprobe material, and the above test was also performed.
[0066] like Figure 3 As shown in Figure 2, the presence of other interfering metal ions did not significantly change the fluorescence intensity of Si-AQ-IIA-1 at 425 nm, indicating that Si-AQ-IIA-1 has excellent recognition specificity and anti-interference performance for zinc ions. Figure 4 ), after adding zinc ions, the fluorescence intensity of Si-AQ-IIA-1 at 425nm increased more significantly, and Si-AQ-IIA-1 prepared by surface ion imprinting technology had higher fluorescence detection sensitivity. In addition, the addition of the same interfering ions caused greater interference to the detection results of Si-AQ-NIIA prepared by non-ionic imprinting technology, and the fluorescence enhancement of the material containing zinc mixed ions was much smaller than the fluorescence enhancement caused by a single zinc ion. Therefore, the application of surface ion imprinting technology significantly enhanced the fluorescence detection selectivity of the nanoprobe material for zinc ions in water. This characteristic indicates that the phenanthroline-modified nano-silica fluorescent probe based on surface ion imprinting technology has broad application prospects in the field of selective fluorescence detection of zinc ions in water.
Claims
1. A quinoline-modified nano-silica zinc ion fluorescent probe based on surface imprinting technology, wherein a quinoline ligand-imprinted cavity structure having high complementarity with zinc ions in shape and size is fixed on the outer surface of nano-silica particles by the surface ion imprinting method, so as to achieve specific recognition and adsorption enrichment of target zinc ions. According to the different positions of the amide bond in the quinoline chromophore substitution, the general structural formula is as follows: in, Refers to the outer surface of nano-white carbon black particles. It is a specific imprinted cavity structure with high complementarity in shape and size with the zinc ion, and the amide bond is located at one of the four substitution sites of the benzene ring in the quinoline chromophore.
2. The quinoline-modified nano-silica zinc ion fluorescent probe based on surface imprinting technology according to claim 1, characterized in that: The preparation method comprises the following steps: Step 1: Add a certain amount of aminoquinoline and triethylamine to a round-bottom flask containing an organic solvent, cool to 0°C and stir magnetically for 20 to 60 minutes, then slowly drop acetyl halide into the solution through a dropping funnel over 20 to 60 minutes; slowly heat the mixed solution to room temperature and stir magnetically for overnight reaction, then remove the organic solvent in the reaction system by vacuum rotary evaporation, and separate and purify the crude product by silica gel column chromatography to obtain AQ-X. The specific synthesis step reaction formula is expressed as follows: Step 2: Add equal amounts of AQ-X and (3-aminopropyl) triethoxysilane obtained in step 1 to a round-bottom flask containing an organic solvent, stir magnetically to mix evenly, and then add potassium carbonate; stir the reaction solution magnetically and reflux for 12 to 24 hours, refrigerate and stand at 5°C for 12 hours, filter the solution to remove white insoluble matter, and remove the solvent from the filtrate by vacuum rotary evaporation to obtain a yellow oil; dissolve the obtained yellow oil in anhydrous ethanol, add a certain amount of zinc nitrate to the solution as a template imprinted metal ion, wherein the amount of zinc nitrate is 1 / 2 of the amount of (3-aminopropyl) triethoxysilane; control the temperature at 40 to 50°C under nitrogen protection and stir magnetically for 12 to 24 hours, remove ethanol in the reaction system by vacuum rotary evaporation, and obtain a complex AQ(Zn) of quinoline functionalized siloxane coupling agent monomer and zinc ion template. The specific synthesis step reaction formula is expressed as follows: Step 3, AQ (Zn) in step 2 and acidified fumed nano-silica are dispersed in an organic solvent, and after ultrasonic dispersion, the mixture is magnetically stirred at 60 to 90° C. under nitrogen protection for 12 to 24 hours; after cooling to room temperature, the product is centrifuged, and the obtained solid is washed twice with tetrahydrofuran and then twice with ethanol, and finally vacuum dried to obtain a nano-silica material Si-AQ (Zn) with a surface-modified quinoline chromophore coordinated with zinc ions. The specific synthesis step reaction formula is expressed as follows: Step 4: Add Si-AQ(Zn) in step 3 to an inorganic acid solution, and after ultrasonic dispersion, magnetic stirring is performed at room temperature for 12 to 24 hours, and the product is centrifuged; the obtained solid is repeatedly washed with deionized water until the washed aqueous solution is close to neutral; and finally, vacuum drying is performed to obtain quinoline-modified nano-silica fluorescent probe Si-AQ-IIA based on surface ion imprinting technology. The specific synthesis step reaction formula is expressed as follows:
3. The quinoline-modified nano-silica zinc ion fluorescent probe based on surface imprinting technology according to claim 2, characterized in that: In step 1, the aminoquinoline is selected from any one of 5-aminoquinoline, 6-aminoquinoline, 7-aminoquinoline or 8-aminoquinoline; the ratio of the amount of the aminoquinoline substance to the amount of triethylamine is 1:1.0-1.2; the organic solvent is selected from any one of dichloromethane, chloroform, acetone, methanol, anhydrous ethanol, isopropanol, anisole, tetrahydrofuran, dioxane, acetonitrile or N,N-dimethylformamide; the solid-liquid mass volume ratio of the aminoquinoline and the organic solvent is 1:100-150 g / mL; the halogenated acetyl halide is selected from any one of chloroacetyl chloride, bromoacetyl bromide, bromoacetyl chloride or chloroacetyl bromide; the ratio of the amount of the aminoquinoline substance to the amount of the halogenated acetyl halide is 1:1.0-1.
2.
4. The quinoline-modified nano-silica zinc ion fluorescent probe based on surface imprinting technology according to claim 2, characterized in that: In step 2, the organic solvent is selected from any one of dichloromethane, chloroform, acetone, methanol, anhydrous ethanol, isopropanol, anisole, tetrahydrofuran, dioxane, acetonitrile or N,N-dimethylformamide; the solid-liquid mass volume ratio of the (3-aminopropyl) triethoxysilane and the organic solvent is 1:100-150 g / mL; the molar ratio of the (3-aminopropyl) triethoxysilane and potassium carbonate is 1:1.5-2.5; the solid-liquid mass volume ratio of the (3-aminopropyl) triethoxysilane and ethanol is 1:100-150 g / mL.
5. The quinoline-modified nano-silica zinc ion fluorescent probe based on surface imprinting technology according to claim 2, characterized in that: Step 3: The mass ratio of AQ (Zn) to nano-silica is 1:1.0-1.5; the organic solvent is selected from any one of dichloromethane, chloroform, acetone, methanol, anhydrous ethanol, isopropanol, anisole, tetrahydrofuran, dioxane, acetonitrile or N,N-dimethylformamide; the solid-liquid mass volume ratio of the nano-silica to the polar organic solvent is 1:100-150 g / mL.
6. The method for preparing a quinoline-modified nano-silica zinc ion fluorescent probe based on surface imprinting technology according to claim 2, characterized in that: Step 4: The inorganic acid solution is selected from any one of sulfuric acid, hydrochloric acid or nitric acid solution; the solid-liquid mass volume ratio of the Si-AQ (Zn) to the inorganic acid solution is 1:80-120 g / mL; and the mass concentration of the inorganic acid is 0.3-1.0%.
7. An application of quinoline-modified nano-silica zinc ion fluorescent probe based on surface imprinting technology, characterized in that: The nano-silica zinc ion fluorescent probe combines with zinc ions in water and loads the ions on the surface of the material, and fluorescence enhancement occurs at the same time. Therefore, the quinoline-modified nano-silica zinc ion fluorescent probe based on surface imprinting technology can be used for selective fluorescence identification and detection of zinc ions in water.